Genetic Engineering of the Rock Inhabitant Knufia petricola Provides Insight Into the Biology of Extremotolerant Black Fungi - Erdmann, Eileen A.; Nitsche, Sarah; Gorbushina, Anna A.; Schumacher, Julia (Frontiers in Fungal Biology, 2022)
Black microcolonial fungi (Ascomycetes from Arthonio-, Dothideo-, and Eurotiomycetes) are stress-tolerant and persistent dwellers of natural and anthropogenic extreme habitats. They exhibit slow yeast-like or meristematic growth, do not form specialized reproduction structures and accumulate the black pigment 1,8-dihydroxynaphthalene (DHN) melanin in the multilayered cell walls. To understand how black fungi live, survive, colonize mineral substrates, and interact with phototrophs genetic methods are needed to test these functions and interactions. We chose the rock inhabitant Knufia petricola of the Chaetothyriales as a model for developing methods for genetic manipulation. Here, we report on the expansion of the genetic toolkit by more efficient multiplex CRISPR/Cas9 using a plasmid-based system for expression of Cas9 and multiple sgRNAs and the implementation of the three resistance selection markers genR [geneticin/nptII], baR [glufosinate/bar] and suR [chlorimuron ethyl/sur]. The targeted integration of expression constructs by replacement of essential genes for pigment synthesis allows for an additional color screening of the transformants. The black-pink screening due to the elimination of pks1 (melanin) was applied for promoter studies using GFP fluorescence as reporter. The black-white screening due to the concurrent elimination of pks1 and phs1 (carotenoids) allows to identify transformants that contain the two expression constructs for co-localization or bimolecular fluorescence complementation (BiFC) studies. The co-localization and interaction of the two K. petricola White Collar orthologs were demonstrated. Two intergenic regions (igr1, igr2) were identified in which expression constructs can be inserted without causing obvious phenotypes. Plasmids of the pNXR-XXX series and new compatible entry plasmids were used for fast and easy generation of expression constructs and are suitable for a broad implementation in other fungi. This variety of genetic tools is opening a completely new perspective for mechanistic and very detailed study of expression, functioning and regulation of the genes/proteins encoded by the genomes of black fungi.